2012
DOI: 10.1111/j.1600-0714.2012.01187.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesized Pheophorbide a‐mediated photodynamic therapy induced apoptosis and autophagy in human oral squamous carcinoma cells

Abstract: Background:  Pheophorbide a (Pa) is a chlorine‐based photosensitizer derived from an ethnopharmacological herb, and our group recently synthesized Pa by the removal of a magnesium ion and a phytyl group from chlorophyll‐a. In this study, the effect of photodynamic therapy (PDT) with synthesized Pa was examined in a human oral squamous cell carcinoma (OSCC) cells. Methods:  Cells were treated with PDT with Pa, and reactive oxygen species (ROS) and mitochondrial membrane potential [ΔΨ (m)] were examined. Apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…Recently, accumulating evidence indicated that ROS, the direct cytotoxic agents of PDT, can also stimulate autophagy with functional consequences varying from cytoprotection to the activation of autophagic cell death . This finding is consistent with the conclusions of the research groups of Kessel D and Ahn MY; they also found PDT could induce autophagy in cancer cells . Furthermore, in this study, we found chlorophyllin f would distribute in the lysosomes of 5637 and T24 cells, which also indicated that f‐PDT might induce autophagy in the two cell lines.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, accumulating evidence indicated that ROS, the direct cytotoxic agents of PDT, can also stimulate autophagy with functional consequences varying from cytoprotection to the activation of autophagic cell death . This finding is consistent with the conclusions of the research groups of Kessel D and Ahn MY; they also found PDT could induce autophagy in cancer cells . Furthermore, in this study, we found chlorophyllin f would distribute in the lysosomes of 5637 and T24 cells, which also indicated that f‐PDT might induce autophagy in the two cell lines.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, we synthesized pheophorbide a (Pa) by removing a magnesium ion and a phytyl group from chlorophyll-a. Our studies reported that Pa-based PDT can effectively inhibit tumor cell proliferation in several cancer cells, including skin and head and neck cancer (16)(17)(18). Other research groups reported that Pa-based PDT can effectively inhibit tumor cell proliferation in hepatocellular carcinoma (19,20), colon cancer (21), pigmented melanoma (22) and breast adenocarcinoma (23); however, its therapeutic potential in oral cancer (especially instances of MDR) has not been fully investigated.…”
Section: Introductionmentioning
confidence: 85%
“…24) PDT involves the interaction of photosensitizers, light and oxygen. 25) PDT was reported to inhibit cancers through different cell death pathways. 26) In this study, ALA-PDT significantly suppressed A431 cell proliferation via inducing mitochondria-dependent intrinsic pathway cell apoptosis, which was evidenced with up-regulation of active caspase 3, Bax, active caspase 9 and Afaf1 levels, and down-regulation of Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with study from Mee et al, who reported that Pa (a kind of Photosensitizer)-PDT exerted anti-tumor effects by inducing apoptosis and autophagy, and autophagy inhibition enhances Pa-PDT-mediated apoptosis in human oral squamous carcinoma cells. 25)…”
Section: Discussionmentioning
confidence: 99%